A Dual‐Responsive Antibiotic‐Loaded Nanoparticle Specifically Binds Pathogens and Overcomes Antimicrobial‐Resistant Infections. Issue 9 (22nd January 2021) - Ye, Mingzhou; Zhao, Yi; Wang, Yuyuan; Zhao, Miao; Yodsanit, Nisakorn; Xie, Ruosen; Andes, David; Gong, Shaoqin
Abstract: Antimicrobial resistant (AMR) infections are a growing threat to public health and there is a general lack of development in new antibiotics. Here, a dextran‐coated stimuli‐responsive nanoparticle (NP) that encapsulates the hydrophobic antibiotic, rifampicin, and specifically binds bacteria to overcome AMR infections is reported. The NP shows a strong affinity with a variety of pathogens in vitro and effectively accumulates in the bacterial infected tissues. The NP is activated by either low pH or high reactive oxygen species in the infectious microenvironment, and releases both cationic polymer and rifampicin that display synergistic activity against AMR pathogens. The NP carrier also enables the antibiotic to penetrate both bacterial biofilms and mammalian cells, thus allowing the elimination of biofilm and intracellular infections. The NP formulation demonstrates both safety and efficacy in two animal infection models against either Gram‐negative or Gram‐positive AMR pathogens. Abstract : A dextran‐coated polymeric nanoparticle is developed to target and eliminate antimicrobial‐resistant pathogens. The NP can bind to lectins expressed by bacteria and accumulate in the infected tissues, releasing the antimicrobial in response to the inflammatory microenvironment, and overcoming antimicrobial resistance. The NP can eliminate biofilm and intracellular infections, and exhibits remarkable in vivo efficacy in treating antimicrobial‐resistant infections.